Subspecies and Distribution. D.t.torquatusPallas,1779—NEEuropeanRussiaandW&CSiberia(WofYeniseiRiver). D.t.chionopaesG.M..Allen,1914—ESiberia(EofYeniseiRiver),includingBolshevikIandNewSiberianIs,EtoChukchiandKamchatkapeninsulas. D. t. ungulatus Baer, 1841 — Novaya Zemlya I (N Russia). in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Subspecies and Distribution. D.t.torquatusPallas,1779—NEEuropeanRussiaandW&CSiberia(WofYeniseiRiver). D.t.chionopaesG.M..Allen,1914—ESiberia(EofYeniseiRiver),includingBolshevikIandNewSiberianIs,EtoChukchiandKamchatkapeninsulas. D. t. ungulatus Baer, 1841 — Novaya Zemlya I (N Russia). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 299, DOI: 10.5281/zenodo.6707142 ...